Model Restorative Justice dalam Diversi Anak Menggunakan Pendekatan Yuridis-Empiris - Jesari, Jihan; Aliya, Yuni (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The Indonesian juvenile justice system has increasingly recognized the importance of restorative justice as an alternative to retributive approaches, with diversion serving as a key instrument to protect children’s rights and ensure the best interests of the child. This study aims to analyze judges' roles in implementing diversion and to formulate a conceptual model that integrates normative legal provisions with empirical practices. Using a juridical-empirical approach, the research combines normative analysis of the Child Criminal Justice System Law and related regulations with empirical data obtained from in-depth interviews, courtroom observations, and judicial decisions across several district courts. The findings reveal significant variations in the implementation of diversion, influenced mainly by judges’ interpretations, children’s psychological conditions, family support, and victims’ involvement. While normative frameworks strongly guide judicial decisions, non-legal factors are equally decisive in determining the success of diversion. The study contributes theoretically by offering an integrated model of restorative justice in Indonesian juvenile courts and, practically, by recommending strengthening judges’ capacity, providing mediation facilities, and increasing victim participation. This research concludes that diversion in Indonesia should be understood not only as a legal obligation but also as a restorative mechanism that ensures balanced recovery for children, victims, and society.